Non-Mendelian inheritance of macronuclear mutations is gene specific in Paramecium tetraurelia. - Scott, J M (1994)
Paramecium tetraurelia contains two types of nuclei, a diploid germinal micronucleus and a large transcriptionally active macronucleus. The macronuclear genome is formed from the micronuclear DNA during sexual reproduction. Previous studies have shown that the processing of the A-type variable surface protein gene during formation of a new macronucleus is dependent on the presence of the A gene in the old macronucleus. It is not clear if this is a general feature that controls the formation of the Paramecium macronuclear genome or a unique feature of the A locus. Using micronuclear transplantation, we have constructed a strain that has a wild-type micronucleus but has macronuclear deletions of the A- and B-type surface protein genes. Neither the A nor the B gene is incorporated into the new macronucleus after sexual reproduction. Macronuclear transformation of this strain with the B gene rescues the B-gene deletion after formation of the next macronucleus but has not effect on the A deletion. Similarly, transformation with the A gene shows gene-specific rescue for A but not B. The effect of the old macronucleus on the processing of the new macronucleus results in a pattern of non-Mendelian inheritance of both macronuclear deletions. Progeny from the wild-type exconjugant are all wild type, and progeny from the A- B- exconjugant are mutant. The features of this A- B- non-Mendelian mutant demonstrate that the regulation of macronuclear DNA processing is gene specific, and our results open the possibility that this type of regulation affects many regions of the Paramecium genome.